Representation of Liberal Feminism in Character of Lady Diana in Spencer Movie - Ecy Pitriani Sulastri; Fina Amalia Masri (English Literature Study Program, Faculty of Humanities, Universitas Halu Oleo, 2024)
This study is intended to analyze the representation of liberal feminism in the character of Lady Diana in the Spencer movie based on the theory of liberal feminism by Mary Wollstonecraft, focusing on the elements of marginalization, subordination, mental or physical violence, and domestication. The objective of this research is to describe “how the representation of liberal feminism in the character of Lady Diana in the Spencer movie.” The researcher used Liberal Feminism by Mary Wollstonecraft to analyze the data. This research used a descriptive qualitative method. The source of the data in this research was taken from the movie entitled Spencer. The data was collected through watching movies repeatedly, screen-shooting and note-taking, identifying and classifying, and then analyzed by presenting, describing, and interpreting as well as concluding the analysis result. As a result of the analysis, the researcher discovered 14 data from the movie that have marginalization, subordination, and mental or physical violence. Meanwhile, there is no domestication that the character of Lady Diana founded. The data found refers to showing the struggle of the character Lady Diana in the movie against marginalization, subordination, and mental violence. Therefore, mental violence becomes the most dominant that Lady Diana faces in this movie.